The assesment of women – breast cancer survovors’ sense of health security - Kołłątaj, Witold; Kołłątaj, Barbara; Karwat, Irena D. (Polish Journal of Public Health, 2011)
Introduction. The number of breast cancer survivors increases annually. Despite the official completion of the therapy, cancer survivors contend with numerous problems throughout the remaining years of their lives. Aim. The aim of this study was to assess the sense of health security reported by patients who had finished hospital therapy for breast cancer. Material and methods. The tested group consisted of 116 women – members of the Amazon Women Association-Lublin, aged 35-82, with breast cancer diagnosed in 1992-2008. A questionnaire-based method was used. A special original survey questionnaire with questions directed to breast cancer survivors was applied. Results. The obtained data suggest that the surveyed women have got many reservations about the state of medical, psychological and social care. The fewest reservations were expressed about the availability and content of brochures addressed to women after mastectomy, access to free rehabilitation procedures (56%) as well as to free medical advice in the field of oncology (46%). Only 28% of respondents were satisfied with the availability of medical care provided by other medical specialists. Less than 50% of women were fully satisfied with the access to free laboratory tests. The most negative opinions concerned the availability of psychological and social care. Conclusions. Women after breast cancer have got special medical as well as psychological and social needs. Many of these needs are not fulfilled. Significant changes in the functioning of health and social care must be provided to improve the status quo.